Efficacy and safety of nivolumab in combination with ipilimumab in Japanese patients with advanced melanoma: An open-label, single-arm, multicentre phase II study. (December 2018) - Namikawa, Kenjiro; Kiyohara, Yoshio; Takenouchi, Tatsuya; Uhara, Hisashi; Uchi, Hiroshi; Yoshikawa, Shusuke; Takatsuka, Sumiko; Koga, Hiroshi; Wada, Naoko; Minami, Hironobu; Hatsumichi, Masahiro; Asada, Suguru; et al.
Abstract: Aim: The aim of the study was to evaluate the efficacy and safety of nivolumab combined with ipilimumab in treatment-naïve Japanese patients with advanced melanoma. Methods: In this multicentre, single-arm study, treatment-naïve Japanese patients with unresectable stage III/IV or recurrent melanoma received nivolumab (1 mg/kg) plus ipilimumab (3 mg/kg) every 3 weeks for four doses, followed by biweekly doses of nivolumab (3 mg/kg). The primary end-point was centrally assessed objective response rate (ORR). Secondary end-points included overall survival (OS), progression-free survival (PFS), disease control rate and safety. Results: The subtypes of the thirty patients enrolled were: 12, mucosal; eight, non-acral cutaneous; seven, acral; two, uveal and one, unknown primary melanoma. The ORR was 43.3% (95% confidence interval [CI]: 25.5, 62.6) with central and local assessment. The centrally and locally assessed disease control rate (95% CI) were 73.3% (54.1, 87.7) and 86.7% (69.3, 96.2), respectively. At the median follow-up period of 14.1 months (range 5.2–27.7), median OS and centrally assessed PFS were not reached. OS (95% CI) at 6, 12, 18 and 24 months was 93.3% (75.9, 98.3), 83.3% (64.5, 92.7), 72.9% (50.0, 86.5) and 65.6% (40.4, 82.2), respectively. Treatment-related adverse events (AEs) occurred in all patients. Grade III–IV and serious AEs occurred, mostly during the combination phase, in 23 (76.7%) and 20 (66.7%) patients, respectively. No treatment-related deaths occurred. Conclusions: This study confirmed the efficacy and safety of nivolumab plus ipilimumab in treatment-naïve Japanese patients with advanced melanoma including rare subtypes. Incidence rates for grade III–IV AEs were high but manageable with appropriate medical attention and treatment. Trial registration: JapicCTI-152869. Highlights: This study tested the efficacy and safety of nivolumab plus ipilimumab. Participants were treatment-naïve Japanese patients with advanced melanoma including rare subtypes. Survival outcomes were consistent with previous studies in Western populations. The safety profile was similar to previous reports. Nivolumab plus ipilimumab is a viable option for Japanese melanoma patients.